TRANSITION FROM OPEN PIT COAL MINE TO THE UNDERGROUND MINE IN SOFT ROCKS - Narmatov Akhror, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
To achieve a successful and effective operation, the transition from open pit to underground mining requires accurate planning and analysis. Numerical modeling utilizing programs like FLAC3D has been an important tool for simulating and analyzing the complicated geomechanical behavior connected with this shift in recent years. The use of FLAC3D to develop a model for the switch from open pit coal mining to underground coal mining in soft rocks with using room and pillar mining method is explored in this abstract. It presents the development of model to analyze and simulate the complex dynamics of this transition. The significant considerations that went into developing the model, such as geotechnical characteristics, rock mass behavior, and mine design parameters, are highlighted in the abstract. It highlights how essential proper input data are to producing reliable simulations and forecasts in soft rocks. The usage of FLAC3D for tracking pit wall stability during the transition period, evaluating the influence on nearby infrastructure, and optimizing underground mine design are covered in the abstract. The model's flexibility allows the investigation of various conditions and offers valuable insight about the transition process. The research emphasizes the potential of the FLAC3D model to lead decision-making during the transition from open pit to underground mining through detailed analysis like choosing appropriate width for main entrance and cross section stopes and their interpretation. It emphasizes how important it is to understand the geomechanical behavior of the coal deposit, optimize the mine's design parameters, and ensure safety for employees. The room and pillar method is utilized to recover coal resources from deep underground mines, and the results from the model can help improve efficiency, sustainability, and risk prevention.